Comparing learning opportunities of generic skills in higher education to the requirements of the labour market - Lohberger, Katharina; Braun, Edith (Frontiers in Education, 2022)
In research on higher education, the link between education and future professional success is well documented. Little research, however, has been done about existing learning opportunities at institutions of higher education that help students acquire generic skills and on the fit between such learning opportunities and labour market demands. To address these questions, we adapted an existing scale for assessing areas of generic skills, which originated in research on job requirements, and transferred it to a survey of students (N=4,258). We also implemented a comparable questionnaire, assessing the same set of generic skills, in a graduate survey (N=378). The results of our study show that by using a theoretical model such as this, it is possible to connect student and graduate surveys related to generic skills. Factor analysis provides evidence for the theoretical expected areas for students. Cluster analysis of student data suggests that learning opportunities for generic skills differ according to field of study. We conclude by discussing our study’s limitations and implications.